Interactive Relationship between Silver Ions and Silver Nanoparticles with PVA Prepared by the Submerged Arc Discharge Method - Kuo-Hsiung Tseng; Chih-Ju Chou; To-Cheng Liu; Der-Chi Tien; Tong-chi Wu; Leszek Stobinski (Advances in Materials Science and Engineering)
This study uses the submerged arc discharge method (SADM) and the concentrated energy of arc to melt silver metal in deionized water (DW) so as to prepare metal fluid with nanoparticles and submicron particles. The process is free from any chemical agent; it is rapid and simple, and rapid and mass production is available (0.5 L/min). Aside from the silver nanoparticle (Ag0), silver ions (Ag+) exist in the colloidal Ag prepared by the system. In the preparation of colloidal Ag, polyvinyl alcohol (PVA) is used as an additive so that the Ag0/Ag+ concentration, arcing rate, peak, and scanning electron microscopic (SEM) images in the cases with and without PVA can be analyzed. The findings show that the Ag0/Ag+ concentration increases with the addition level of PVA, while the nano-Ag and Ag+ electrode arcing rate rises. The UV-Vis absorption peak increases Ag0 absorbance and shifts as the dispersity increases with PVA addition. Lastly, with PVA addition, the proposed method can prepare smaller and more amounts of Ag0 nanoparticles, distributed uniformly. PVA possesses many distinct features such as cladding, dispersion, and stability.